(untitled) (Journal of the Bangladesh Agricultural University, 2013)
Repellency effect of turmeric and neem was investigated against the mite Necrobia sp. and field doses were determined on the basis of their repellency, keeping quality, insect occurrence and sensory evaluation of turmeric and neem treated dry fish and their cooked products. Turmeric and neem were used in three forms, viz., i. extract, ii. powder and iii. pellet. The concentrations tested for turmeric and neem extracts were 2%, 3%, 4% and 3%, 5%, 7%, respectively, those of both powders were 1.0%, 1.5% and 2.0% and both pellets were 1, 2, 3 pieces on 100 g dry fish. The order of repellency among three products were: extract> powder> pellet. Turmeric extract and powder were more repellent than neem extract and powder. The color, odor, texture and general appearance of the untreated control and treated dry fish were almost similar after 2 month of storage at room temperature. After 4 month of storage, the sensory attributes like odor, texture and general appearance and the occurrence of insects in control dry fish fell down significantly but those in treated dry fish were mostly unchanged. Study suggested that turmeric at the rate of 3% extract or 1.5% powder or neem at the rate 5% extract or 1.5% powder could be suitable field doses for application of such herbs in dry fish directly to repel insects while storing the products. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14927 J. Bangladesh Agril. Univ. 10(2): 339-348, 2012